Selection of various coagulants for sugar industry wastewater treatment - Samsudin, Nur Shazweena; Kabbashi, Nassereldeen Ahmed; Jami, Mohammed Saedi (IIUM Press, 2019)
Sugar industry is one of the industries that produce a high amount of pollutant since its wastewater contains high amount of organic material, Biochemical Oxygen Demand (BOD) and Chemical Oxygen Demand (COD). If this waste is discharged without a proper treatment into the watercourse, it can cause problem to aquatic life and environment. For the primary treatment process, sugar wastewater can be treated by using chemical precipitation method which involves coagulation process. Currently, ferric chloride has been used as the coagulant but it consumes more alkalinity and corrosive. In this study, the suitable coagulant to be used to treat the wastewater from sugar industry and the optimum conditions to achieve high percentage removal of COD was determined. The characteristic of the wastewater was firstly determined. Then, the most suitable coagulant to be used for the treatment was studied by determining their efficiency to reduce COD and TSS in the wastewater at different dosages. Aluminium sulphate (alum), ferric chloride and polyaluminium chloride (PAC) were chosen to be studied for suitable coagulant. The optimum condition of the coagulant (pH, coagulant dosage, fast mixing speed) was determined by using Design Expert software. Results showed that alum can be used to effectively remove 42.9% of COD and 100% of TSS at high dosage (50 mg/l). The optimum condition of alum was at pH 5.2, 10 mg/l of alum and 250 rpm of mixing speed. This shows that at optimum condition, alum can be used to treat wastewater from sugar industry.